1999
DOI: 10.1046/j.1440-1622.1999.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Bile Duct Injuries During Laparoscopic Cholecystectomy: A Collective Experience of Four Teaching Hospitals and Results of Repair

Abstract: The experience of a 0.43% bile duct injury rate is comparable to the best results from most large series in the West. Inflammation at Calot's triangle is an important associated factor for injury. Early recognition and prompt repair affords good results, and hepaticojejunostomy is recommended as the repair of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…The estimated incidence of major bile duct injuries, which was 0.1% to 0.3% [9,10] during the open cholecystectomy era, has risen to an estimated 0.4% to 0.86% [3][4][5][6][7][8]13] for LC. Fletcher et al [8] also found that compared with open cholecystectomy, LC carries a nearly twofold higher risk of major biliary, vascular, and bowel complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated incidence of major bile duct injuries, which was 0.1% to 0.3% [9,10] during the open cholecystectomy era, has risen to an estimated 0.4% to 0.86% [3][4][5][6][7][8]13] for LC. Fletcher et al [8] also found that compared with open cholecystectomy, LC carries a nearly twofold higher risk of major biliary, vascular, and bowel complications.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on predisposing factors for biliary injury during LC suggests that the presence of acute cholecystitis has the strongest correlation [5,16]. However, some reports say this may not be true [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, except one case all the CBD injury patients were controlled promptly. In this study, total 5 (4.71%) cases were converted among 106 patients and the reasons for conversion were bleeding, dense adhesion of gall bladder with CBD, perforated gall bladder with biliary peritonitis and pasted adhesion of gall bladder with Calot's triangle as compared to 16% conversion to open reported by Brodsky et al, 37.8%, 20.5%, 7.7% and 6% respectively by others [17][18][19][20][21] . There was no significant difference found in conversion rate in emergency laparoscopic cholecystectomy (21% ) versus delayed group (24%).…”
Section: Paralytic Ileusmentioning
confidence: 69%
“…Meanwhile, in Cheema's study, 3 bile duct injuries have been reported among 482 cases 9 . However, early recognition and prompt repair gives good results 18 . Male gender and age >60 are liable for more complications 19 .…”
Section: Paralytic Ileusmentioning
confidence: 99%